2019
DOI: 10.1155/2019/5825309
|View full text |Cite
|
Sign up to set email alerts
|

Management of Severe Epistaxis during Pregnancy: A Case Report and Review of the Literature

Abstract: Background Epistaxis is a common problem during pregnancy. Few cases of severe epistaxis, not associated with nasal lesions or clotting disorders, were described in the literature. We reported a case of severe epistaxis in a pregnant patient, exploring all the different possible management options. Case A 33-year-old primigravida, who was 38 weeks pregnant, presented with spontaneous severe left-sided epistaxis. Her blood pressure was into normal ranges. Clotting disorders and nasal lesions were excluded. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Within the scarce available literature on epistaxis in pregnant women, conservative treatments, such as intravenous tranexamic acid administration, nasal packing and bipolar cautery, are generally recommended as first-line measures. If conservative measures fail, surgical care under general anesthesia may need to be considered [13,14]. The question remains, however, whether these recommendations are generalizable to expectant mothers with HHT.…”
Section: Epistaxis During Pregnancy and Delivery In Hht Patientsmentioning
confidence: 99%
“…Within the scarce available literature on epistaxis in pregnant women, conservative treatments, such as intravenous tranexamic acid administration, nasal packing and bipolar cautery, are generally recommended as first-line measures. If conservative measures fail, surgical care under general anesthesia may need to be considered [13,14]. The question remains, however, whether these recommendations are generalizable to expectant mothers with HHT.…”
Section: Epistaxis During Pregnancy and Delivery In Hht Patientsmentioning
confidence: 99%
“…The nasal mucosa is influenced by systemic, local, metabolic or hormonal disorders that cause slowed mucociliary function during pregnancy. [1][2][3] The otolaryngological (ENT) symptoms encountered during pregnancy are most often mild, sometimes indicative of a specific pathology. 1,2 Pregnancy promotes a set of physiological changes in the female body, The ENT organs undergo the influence of its changes by certain manifestations within it such as rhinitis, epistaxis, and some disorders of the inner ear.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The otolaryngological (ENT) symptoms encountered during pregnancy are most often mild, sometimes indicative of a specific pathology. 1,2 Pregnancy promotes a set of physiological changes in the female body, The ENT organs undergo the influence of its changes by certain manifestations within it such as rhinitis, epistaxis, and some disorders of the inner ear. 1,2,4 Prevalence of epistaxis in non-pregnant female population is estimated at 6%, but this rate doubles in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…El Goulli et al in 1979 [1] reported on a case of severe epistaxis in pregnancy with maternal collapse and fetal death. From then on few case reports have been published) [1-9] (Table 1) with different management of epistaxis in third trimester of pregnancy. Furthermore, the mode of delivery, vaginally or by cesarean section, varies in this short report, probably due to qualitative and quantitative levels of blood loss.…”
Section: Introductionmentioning
confidence: 99%
“…Epistaxis is a common problem in pregnancy, secondary to an increased nasal mucosa vascularity. A large volume epistaxis is uncommon in women without risk factors (such as anticoagulants therapy or blood clotting disorders) [9]. When severe blood loss through the nose occurs in third trimester of pregnancy there are different therapeutical approaches: nose packing, hemostatic foam/sponge, cautery or diathermy, ligation of sphenopalatine artery.…”
Section: Introductionmentioning
confidence: 99%